Car workshop.com system - Nur Amalina, Abdul Halim (2019)
Car Workshop.com System is a system that especially design to the customer to book their appointment date of servicing the car at anytime and anywhere. The common problem faced is customer need to be waiting for a long time just to follow the queue who arrive first will get their car to be service first. Thus, the objective of this project is to develop a web-based system especially for car workshop that also can be used by customer for example to book an appointment to service their car. Car Workshop.com System is develop by using C# programming language and the system is tests using User Acceptance Test in order to know whether the system meets with requirements that needed by the customer or not. The methodology used for this study is Rapid Application Development which more emphasizing the rapid development of the prototyping and user interface for a short time of delivering the system. RAD allow the early system to be integrate together and can get constant user feedback from the user. After the system is fully developed, testing is be done by using User Acceptance Test in order to know whether the system meets with user requirements or not and to detect the error or bugs so that it can be fixed before deliver the system to the external environment. The test is to ensure that the system already achieved the objective and all function work accordingly and also able to solve the problem statement. As the result, a web based system for the car workshop are developed that allow customer to book an appointment beforehand, calculate the overall estimation cost and more.